The rating of perceived challenge- the relationship between player and coach perceptions of rugby training - Bam, Jenna (Department of Human Biology, 2023)
Introduction: Monitoring training is a common practice in sport, however skill training is not periodised and monitored to the same extent as physical training. Furthermore, it is important that the coach's and player's understanding of the training load is alike to avoid maladaptation and to modify future training sessions. The first part of this thesis aims to synthesise research that investigates the relationship between coach RPE and player RPE by means of a systematic review. The second part is an original study that uses a technical skill measurement (rating of perceived challenge, RPC) and tests (i) the relationship between player and coach RPC, (ii) the relationship between player session rating of perceived exertion (sRPE) and RPC, and (iii) the differences between backs and forwards for sRPE and RPC, within gym and field-based training sessions. Methods: For the systematic review, 4915 articles were retrieved from 4 databases using the following search terms: Train*) OR (‘Training-Load') OR (‘Load-monitoring') OR (‘training-load-monitoring') AND (‘Internal-load') OR (‘subjective-ratings') OR (‘perception-of-effort') OR (‘perceived-exertion') OR (‘perceived-stress') AND (Coach*) OR (Player*) OR (Player*). After duplicates were removed a total of 1591 articles were reviewed for inclusion. Studies that reported the relationship, association, difference or agreement between the player and coach were included in the systematic review which amounted to 25 articles. For the second part of the thesis, fifty-one (n=51) male u21 rugby union players' sRPE and RPC scores were collected after team, split, and gym sessions. The coaches' (n=4) RPC ratings were only collected after team sessions and split sessions. This equated to a total number of 1798 observations over 11 weeks (a total of 66 training sessions). Results: The systematic review reported a range of correlations and differences between player and coaches' perception of training. Coaches both overestimated and underestimated session intensities. A weak positive relationship (rho= 0.30; p< 0.01) was found between player RPC (4.30 ± 1.60 AU) and coach RPC (4.95 ± 1.32) for team sessions, while a moderate positive relationship (rho= 0.47; p< 0.05) was found for split sessions (player RPC 4.32 ± 1.84 AU; coach RPC 4.19 ± 1.49 AU). A moderate positive relationship (rho= 0.67; p< 0.05) was found between player RPC (4.32 ± 1.84 AU) and player sRPE (4.57 ± 1.59 AU) for split sessions, as well as for team sessions (RPC 4.95 ± 1.32 AU; sRPE 5.53 ± 1.51 AU; rho= 0.47; p< 0.01). Forwards reported higher RPC (5.32 ± 1.58 AU) compared to backs (3.35 ± 1.53 AU) for split and team sessions (forward's RPC 4.83 ± 1.49 AU; backs RPC 3.71 ± 1.52 AU). No differences in RPC and sRPE between forwards and backs were found for gym sessions (p> 0.05). Discussion: The systematic review gives insight into the different factors which may influence the relationship between player and coach RPE, such as the player's and coach's experience, the player's age and sex, and the method of data collection. The utility of the RPC may be more meaningful in the skill development focused stages such as coordination training and skill adaptability, where coaches are working with fewer players, and focused on specific technical outcomes.